Pharmacoepidemiological Assessment of Antibiotic Prescribing Practices for Community-Acquired Pneumonia in Children: Influence of Age and Pathogen Distribution (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Community-acquired pneumonia remains one of the leading causes of morbidity in pediatric populations worldwide and continues to pose challenges related to optimal antimicrobial selection. This article provides a comprehensive pharmacoepidemiological evaluation of antibiotic prescribing practices in children with community-acquired pneumonia, with particular focus on the influence of patient age and pathogen distribution. By analyzing patterns of antibiotic use in relation to developmental physiology, epidemiological trends, and microbial etiology, the study aims to identify rational and irrational prescribing behaviors. The findings highlight critical discrepancies between clinical guidelines and real-world practice, emphasizing the need for age-adapted and pathogen-oriented antimicrobial strategies to improve therapeutic outcomes and limit resistance development. This work presents an in-depth pharmacoepidemiological evaluation of antibacterial prescribing patterns for pediatric community-acquired pneumonia, emphasizing how therapeutic decisions vary according to developmental stage and circulating infectious agents. By integrating population-level prescription data with age-related clinical characteristics, the analysis explores the balance between empirical treatment and targeted therapy. Particular attention is given to the consequences of spectrum selection, duration of use, and formulation choice on clinical recovery and antimicrobial safety. The synthesis demonstrates that inappropriate age-independent prescribing contributes to unnecessary exposure and fosters resistance, while rational, stratified approaches improve outcomes and preserve antimicrobial efficacy.